ANALISIS TARIKAN DAN DIAMETER SENAR RAKET BADMINTON TERHADAP PANTULAN SHUTTLECOCK - Arianto, Ivan Setia; Nuri, Nuri; Aji, Mahardika Prasetya; Sulhadi, Sulhadi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Badminton is a popular sport in the world. Racket and string in the Badminton games can not be separated. Many players are often confused in choosing the type of strings and tension the strings in the racket. Selection of the diameter of the strings and tension the racket strings affects the reflection distance shuttlecock. The experiment using a variation of 5 pieces of string diameter of 0.62 mm, 0.64 mm, 0.65 mm, 0.66 mm, 0.68 mm with tension strings and bouncing shuttlecock clearance for the same. The next variation is to use five types of tension strings 22, 23, 25, 27, 29 lbs with a diameter and height same for the distance shuttlecock bouncing. Variation further with starts heights of 100, 150, 200, 250, 300 cm to reflect shuttlecock. The results showed the smaller the diameter of the strings, the higher the reflection distance shuttlecock. The higher the tension of the strings then the distance the lower the reflection shuttlecock. As well as the higher shuttlecock result bounce higher. High string tension or large diameter suitable for the type of players to defende because they have good control. While the low strings tension strings or small diameter suitable for the type of players because they attack the energy efficiency. The results of this experiment to facilitate badminton player in choosing the strings tension and the strings diameter of the badminton racket appropriate type of game. Keywords: racket string, badminton, shuttlecock